Travel behaviour of South African tourism students - Slabbert, Elmarie; Saayman, Melville; Van der Merwe, Peet (University of Stellenbosch. Department of Sport Science, 2012)
When developing and managing tourism products, understanding the travel behaviour of niche markets, such as students can create a competitive advantage for tourism products. The purpose of this research was to determine the travel behaviour of tourism students in South Africa. Surveys were conducted at eight Tertiary Education Institutions offering tourism-related qualifications. Second and third year students at these institutions completed a total of 1062 questionnaires. The statistical analysis entailed descriptive statistics and factor analyses of travel motives and factors influencing holiday choices. The results revealed that students have specific preferences, but also similarities with other studies conducted among other tourist markets. Relaxation was found to be a significant motive for students, but gaining knowledge and learning new things were also very important for this market. When selecting destinations, personal influences (for example, previous visits, popularity and season) as well as predetermined influences (for example, availability of a holiday home, size of the travelling group, availability of time share and purpose of the holiday) played an important role
Keywords: Tourism students; travel motivations; holiday choice sets; factor analysis